ACTING ON COMPLICATIONS IN HEART VALVE REPLACEMENT IN RHEUMATIC FEVER, MINIMIZING RISKS AND GUARANTEEING THE PATIENT'S WELL-BEING: A NARRATIVE REVIEW - Pacheco , Stephanie Oedenkoven; Izéria , Felipe Ziolkoski; Ataide , Cristiane Ferreira; de Santana , Adriana Pinheiro; Pereira , Everton Lira; Moreno , Alzira de Souza; Tavernard , Misael Rosa; Ramos , Samuel Neves; Gomes , Mariana Pimenta; de Souza, Bruna Martins; de Souza, Vanessa Maria Gonçalves (Brazilian Journal of Implantology and Health Sciences, 2025)
Rheumatic fever is an inflammatory disease that can damage the heart valves, in some cases requiring surgical replacement to restore heart function. However, this intervention is not without its complications. This article reviews the main surgical complications in patients undergoing heart valve replacement due to rheumatic fever. The narrative review included nine articles published between 2016 and 2023, selected from databases such as Google Scholar and VHL. Strict inclusion criteria were applied and the results analyzed were systematized in a database. The findings indicate that patients with rheumatic fever are at greater risk of complications after valve replacement. Infective endocarditis is one of the most frequent complications and can cause heart failure and serious embolisms. In addition, the formation of clots in the replaced valves can lead to strokes and other ischemic complications. Residual valve insufficiency, characterized by the inadequate functioning of the new valve, has also been observed, generating inefficient blood flow and symptoms of heart failure. Arrhythmias are another common complication, aggravated by the increased risk in patients with rheumatic fever. The risk of surgical site infections is significant due to the chronic inflammatory nature of the disease, increasing vulnerability to problems such as endocarditis. Prevention and proper management of complications are essential. Careful patient selection, the use of prophylactic antibiotics and post-operative follow-up play a fundamental role in reducing the risks. In addition, controlling inflammation and preventing recurrences of rheumatic fever are crucial in the long term. Patients with rheumatic fever face significant challenges after heart valve replacement, making strategies for early identification and efficient management of complications essential. Collaboration between specialists is essential to promote better outcomes and improve the quality of life of these patients.